Peran Indeks Pembangunan Manusia Berbasis Perspektif Syariah - Asraaf Efendi Batubara; Nur Afria Nanda Safitri; Rizki Wahyudi; Sri Rahayu; Wanhar Nasution; Sari Wulandari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In measuring the welfare of society, we can use the Human Development Index as one of the measurement tools. However, not all aspects can be measured by human development, but at least the Human Development Index can provide an overview of the implementation of development with three basic indicators namely; quality of health, educational attainment, as well as economic level in the form of the level of buying interest in the community. on December 31, it was recorded in data from the Ministry of Home Affairs that Muslims in Indonesia reached 237.53 million. Or right at 86.95 of Indonesia's population of 273.32 million people. However, it is very unprofitable if the people of Indonesia do not become a country with a prosperous society. With the largest Muslim population in the world, it is not something that is taboo if Indonesia pays special attention to economic development with sharia principles, considering that Islam is a universal religion, it certainly does not hinder diversity. Keyword: The human development index, welfare, sharia